A case report of IgA-mediated anti-Laminin-γ1 (p200) pemphigoid successfully treated with stapokibart combined with corticosteroids - Zhang, Ting; Liu, Yanhong; Zhang, Zhaohuai; Wang, Ying; Lin, Zhimin; Nie, Zhenhua; Li, Chen; Zhao, Zuotao (Frontiers in Immunology, 2026)
IgA-mediated Anti-Laminin-γ1 (p200) pemphigoid is a rare subtype of subepidermal autoimmune blistering disease (AIBD) characterized by IgA autoantibodies targeting the laminin γ1 chain, a 200 kDa protein located at the dermal-epidermal junction. Patients typically exhibit skin-dominant blistering lesions, also mucosal involvement has been reported. We report a 73-year-old male patient diagnosed with IgA-mediated anti-Laminin-γ1 (p200) pemphigoid. He initially presented with prominent palmoplantar blisters erosions on the eyelids, lips and face, accompanied by mild pruritus. Skin biopsy demonstrated hyperkeratosis, parakeratosis, acanthosis, subepidermal blister formation, and mild perivascular lymphocytic infiltration in the superficial dermis. Direct immunofluorescence showed C3 deposits on the basement membrane. The patient was initially treated successfully with methylprednisolone. During the second recurrence, he presented with annular erythema topped with blisters and erosions on the lips. Comprehensive pemphigus and pemphigoid antibodies panel test showed Laminin γ1 IgA with a titer of 1:10. The rash recurred when corticosteroids were tapered. The patient was then treated with Stapokibart (CM310) in combination with corticosteroids, leading to complete resolution of the skin lesions and successful tapering of the corticosteroids. This case represents the first successful treatment of IgA-mediated anti-Laminin-γ1 (p200) pemphigoid using Stapokibart in combination with corticosteroid.